(untitled) - Watt, S. B. (Simon B.) (London, 1978)
Describes how cylindrical water storage tanks of up to 150 cubic meter capacity can be built using wire-reinforced cement-mortar. Covers design and planning; costs; standard, recommended and alternative construction methods, and other information.
Keywords: Concrete tanks; Design and construction